Esketamine use for anesthesia induction in an ectopic pregnancy patient with hemorrhagic shock: a case report - Xiaojie Liu; Zhen Hua; He Dong; Yanli Zhuo; Haichen Chu; Tianjun Li (Emergency and Critical Care Medicine)
Abstract. Background. Anesthesia induction is challenging in patients with hemodynamic instability. Esketamine has hypnotic, analgesic, and sympathomimetic effects and is the only anesthetic that can increase sympathetic tension. Therefore, it may be more suitable for patients with hypovolemic shock. Case summary. A 40-year-old female patient presented to the emergency department with new-onset abdominal pain and vaginal bleeding for 2 hours. Menstruation of the patient was regular, her self-reported urine pregnancy test was positive half a month earlier, and she had been diagnosed at another hospital 12 days earlier based on a positive blood human chorionic gonadotropin test. Gynecological ultrasonography demonstrated no pregnancy sac in utero, confirming ectopic pregnancy. Emergency laparoscopy for ectopic pregnancy should be performed immediately. We administered esketamine for induction. Conclusion. Esketamine-based total intravenous anesthesia results in mild hypotension in ectopic pregnancies with hemorrhagic shock.